The effects of technostress creators and organizational commitment among school teachers / Narehan Hassan … [et al.] - Hassan, Narehan; Yaakob, Siti Aisyah; Mat Halif, Mazuin; Abdul Aziz, Rozilah; Abdul Majid, Afiza; Sumardi, Nur Athirah (2018)
In the fast-paced world, information is retrieved and stored efficiently using IT technologies. Due to the constant change and advancement in technology, technostress has become a critical issue in many organizations especially for those who are IT illiterate. This scenario is especially true for school teachers in Malaysia where students’ information is stored and retrieved using a database system and posted online for quick accessibility of files and student management. However, for those who are not IT-skilled, this type of work demand can influence both the employee’s motivation and work commitment. School teachers in Malaysia are found to be overworked and most had to take home their work, especially in updating students’ information. The changing work demands and the need to perform both teaching and administrative duties have resulted in teachers facing a stressful working environment. This is especially true for senior teachers, whose IT skill is often lagging compared to their younger counterparts; hence the term technostress is coined -- not only to teachers but to those who are lacking in IT-related skills. Teachers’ commitment is of utmost importance to produce better workforce for the future. Hence, this study was conducted to examine both the relationship and the effects of techno-stress creators and organizational commitment among school teachers. This study was carried out at six schools in Selangor involving 173 school teachers. The findings revealed that two dimensions of techno-stress creators which were techno-uncertainty and techno-insecurity had positive and significant influence on organizational commitment while all other three elements of techno-stress creators which were techno-overload, techno invasion and techno complexity did not predict teachers’ organizational commitment. The findings also revealed that certain amount of techno-stress can enhance the level of teachers’ commitment.